Asuhan Kebidanan Pada Ibu Nifas Di Rsud Dok II Jayapura Provinsi Papua - Melvina Kakyarmabin; Fauziah.F.Hernanto; Dewi Purwatiningsih (2024)
The purpose of the study was to provide continuous midwifery care (continuity of care) and to document SOAP notes for pregnant women, those giving birth, and those in the postpartum period. The method used the Varney management approach. The patient who was accompanied was Mrs.